Student's Willingness and Perception Towards Online Teaching and Learning Through the Psychoeducational Group Counseling Approach - Marryanah Masandal; Abu Yazid Abu Bakar (Universitas Pendidikan Indonesia (UPI), 2023)
This study aims to assess the willingness and perception of students toward online teaching and the learning process among students through a psychoeducational group counseling approach. This study was carried out due to the occurrence of several psychological issues among respondents, including the difficulty of giving focus to the activities of teaching and learning online. The design of this study is in methodical way, namely by running four group counseling sessions through a psychoeducational approach. The method used to get information from these group counseling sessions is by using related modules such as Introduction Session, Strengths-Weaknesses-Opportunities-Threats (SWOT) Analysis, a Day in Life (as a Time Management), and Fantasy of Success. The study found that, despite some identified constraints, online teaching and learning are still preferred by the respondents in terms of their willingness and perception to embrace this new norm of the teaching and learning process.